2017
DOI: 10.3847/1538-4357/aa618f
|View full text |Cite
|
Sign up to set email alerts
|

SPIRITS 15c and SPIRITS 14buu: Two Obscured Supernovae in the Nearby Star-forming Galaxy IC 2163

Abstract: SPitzer InfraRed Intensive Transients Survey-SPIRITS-is an ongoing survey of nearby galaxies searching for infrared (IR) transients with Spitzer/IRAC. We present the discovery and follow-up observations of one of our most luminous (M . Pre-discovery ground-based imaging revealed an associated, shorter-duration transient in the optical and near-IR (NIR). NIR spectroscopy showed a broad (≈8400 km s −1 ), double-peaked emission line of HeI at 1.083 μm, indicating an explosive origin. The NIR spectrum of SPIRITS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 112 publications
8
31
0
Order By: Relevance
“…SPIRITS 15c, spectroscopically confirmed as an SN Ib/IIb in Jencson et al (2017), is fully consistent with the sample of stripped-envelope SNe in its [4.5] light curve. At [3.6] − [4.5] = 3.0 at peak light, it is the reddest strippedenvelope SN yet observed by Spitzer.…”
Section: Comparison To Spitzer Snesupporting
confidence: 77%
See 2 more Smart Citations
“…SPIRITS 15c, spectroscopically confirmed as an SN Ib/IIb in Jencson et al (2017), is fully consistent with the sample of stripped-envelope SNe in its [4.5] light curve. At [3.6] − [4.5] = 3.0 at peak light, it is the reddest strippedenvelope SN yet observed by Spitzer.…”
Section: Comparison To Spitzer Snesupporting
confidence: 77%
“…As discussed in detail in Jencson et al (2017), SPIR-ITS 15c is a clear example of a confirmed, moderately obscured, CCSN. Our assessment is based primarily on near-IR spectroscopy showing distinct similarity to the Type IIb SN 2011dh, and in particular the presence of a broad (≈ 8400 km s 1 ) double-peaked emission line of He I at 1.0830 µm.…”
Section: The Confirmed and Likely Ccsnementioning
confidence: 84%
See 1 more Smart Citation
“…Another example is the ongoing SPitzer InfraRed Intensive Transients Survey (SPIRITS; Kasliwal et al (2017)), which searches for Ch1/2 transients in 190 nearby galaxies. SPIRITS has also led to the discovery of new SNe: Jencson et al (2017) report two SNe in IC 2163 (not a LIRG) separated by less than two years. This survey, which does not include (U)LIRGS, is confined to the local universe (< 15 Mpc) and only aims to discover transients that can be individually resolved.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible for this source to be a dust-obscured supernova as it would only take an A V on the order of a few magnitudes to dim the event enough to not be detectable in optical surveys (see e.g. Jencson et al 2017). Ultimately, deeper imaging at many wavelengths coupled with sensitive spectroscopic information (e.g., JWST) is needed to more fully understand this enigmatic source.…”
Section: Bright Unknown Sourcementioning
confidence: 99%